Les pratiques funéraires en Pannonie de l'époque augustéenne à la fin du 3e siècle : texte et cartes - Márton, András (Archaeopress Roman archaeology, 2019)
This volume aims to give an overview of Roman burial practices in Pannonia during the Early Roman period through the study of tomb structure, the selection and treatment of grave goods and analysis of human remains. It proposes a synthesis of the published finds to serve as a base for future research in the region.